Comparative performances of the 7th and the 8th editions of the American Joint Committee on Cancer staging systems for intrahepatic cholangiocarcinoma. Issue 6 (14th February 2017) - Spolverato, Gaya; Bagante, Fabio; Weiss, Matthew; Alexandrescu, Sorin; Marques, Hugo P.; Aldrighetti, Luca; Maithel, Shishir K.; Pulitano, Carlo; Bauer, Todd W.; Shen, Feng; Poultsides, George A.; Soubrane, Oliver; et al.
Abstract : Background: We sought to evaluate and validate the 8th edition of the AJCC classification using a multi‐institutional cohort of patients with intrahepatic cholangiocarcinoma (ICC). Methods: Patients undergoing curative‐intent hepatic resection for ICC between 1990 and 2015 at 14 major hepatobiliary centers were included and were staged according to 7th and 8th editions AJCC criteria. Results: A total of 1154 patients underwent liver resection for ICC. When patients were staged using the AJCC 7th edition, T2a, T2b, and T4 patients had a higher hazard ratio (HR) of death compared with T1 (T2a, HR 1.43, P  = 0.004; T2b, HR 1.99, P  < 0.001; T4, HR 2.20, P  < 0.001). T3 patients had a higher HR of death compared with T1 patients (HR 1.30, P  = 0.029) but lower than T2a and T2b. According to AJCC 8th edition, T1b, T2, and T4 patients were at higher risk of death compared with T1a patients (T1b, HR 1.91, P  < 0.001; T2, HR 2.29, P  < 0.001; T4, HR 4.16, P  < 0.001). As in the AJCC 7th edition, AJCC 8th edition T3 patients had a higher HR of death compared with T1 patients (HR 1.65, P   = 0.001) but lower than T1b and T2. AJCC 8th edition. T‐category performed slightly better than AJCC 7th edition with a C‐index of 0.609 versus 0.590. Conclusions: A staging system that perfectly discriminates between stages has not yet been developed, but the AJCC 8th edition was able to better stratify the risk of death of Stage III and T3 patients.